Enhanced Efficiency and Stability of n‐i‐p Perovskite Solar Cells by Incorporation of Fluorinated Graphene in the Spiro‐OMeTAD Hole Transport Layer. Issue 36 (7th August 2022) - Lou, Qiang; Lou, Gang; Guo, Hailing; Sun, Tian; Wang, Chunyun; Chai, Gaoda; Chen, Xia; Yang, Guoshen; Guo, Yuzheng; Zhou, Hang
Abstract: Spiro‐OMeTAD is one of the most used hole transport layers (HTLs) in high efficiency n‐i‐p perovskite solar cells (PSCs). However, due to the unsatisfactory conductivity of pristine Spiro‐OMeTAD, additives such as tert‐butylpyridine (tBP) and lithium bis (trifluoromethylsulfonyl)‐imide (LiTFSI) are required to improve its hole transportation. The hygroscopic nature of these additives inevitably deteriorates the device's stability. Here, it is shown that by adding fluorinated graphene (FG) into the Li‐TFSI and tBP doped Spiro‐OMeTAD, both efficiency and stability of the PSCs are significantly enhanced. Using the FG incorporated Spiro‐OMeTAD HTL, the power conversion efficiency (PCE) of the PSC reaches 21.92%, which is 11.8% higher than the original device. The FG not only improves the hole mobility of Spiro‐OMeTAD but also effectively reduces the amount of lithium ions in the perovskite layer and improves the hydrophobicity of the HTL. The FG incorporating cell shows better stability, maintaining 90% of initial efficiency over a 2400 h test in ambient conditions with 25% humidity. Finally, it is further demonstrated that the valence band of FG incorporated Spiro‐OMeTAD HTL has a positive effect on PSCs with a 2D interfacial layer, achieving an impressive PCE of 23.14% and a Voc of 1.226 V. Abstract : This work reports a p‐type additive, fluorinated graphene, for Spiro‐OMeTAD hole transporting layers, which improves hydrophobicity and suppresses carrier recombination at the Spiro‐OMeTAD/perovskite interface. A perovskite solar cell with fluorinated graphene doped Spiro‐OMeTAD achieves a power conversion efficiency of over 23% and long‐term humidity stability of 4600 h.